PEMBATALAN SERTIFIKAT YANG DITERBITKAN DARI JUAL BELI YANG MELAWAN HUKUM (STUDI PUTUSAN NO.1/Pdt.G/2015/PN.Mrj) - Farsya Fachira Aslam; Anda Setiawati (Fakultas Hukum Universitas Trisakti, 2021)
In reality, non-title holders often discover incidents of land sales and purchases. The land sale and purchase case involving H.M. Noor Habdi and Khairul Mahdi involved a parcel of land registered in Tirani's name as the object. Even though H.M. Noor Habdi did not actually own the property, he secured a land certificate from Tirani's husband in order to obtain a bank loan. However, H.M. Noor Habdi did not return the certificate he had borrowed after Tirani's spouse passed away; instead, he changed the name to his own and sold it to his son, Khairul Mahdi. Tirani and her kids, believing their rights had been violated, launched a case on the grounds urged that the land sale and purchase agreement be terminated after being accused of an illegal act. The findings of the study, the discussion and the conclusion led the judges on the Muaro District Court panel to issue Decision No. 1/Pdt.G/2015/PN.Mrj, which declared that H.M. Noor Habdi's legal transaction of buying and selling Khairul Mahdi was invalid and had no legal standing. However, Tirani's side had file a lawsuit with the State Administrative Court (PTUN) in order have the certificate that had been granted Khairul Mahdi's name revoked.